HMAC based one time password generator - Yakut, Selman; Ozer, A. Bedri (IEEE Computer Society, 2014)
One Time Password which is fixed length strings to perform authentication in electronic media is used as a one-time. In this paper, One Time Password production methods which based on hash functions were investigated. Keccak digest algorithm was used for the production of One Time Password. This algorithm has been selected as the latest standards for hash algorithm in October 2012 by National Instute of Standards and Technology. This algorithm is preferred because it is faster and safer than the others. One Time Password production methods based on hash functions is called Hashing-Based Message Authentication Code structure. In these structures, the key value is using with the hash function to generate the Hashing-Based Message Authentication Code value. Produced One Time Password value is based on the This value. In this application, the length of the value One Time Password was the eight characters to be useful in practice. © 2014 IEEE.
HMAC tabanli tek kullanimlik şifre üreteci
2014 22nd Signal Processing and Communications Applications Conference, SIU 2014 -- 23 April 2014 through 25 April 2014 -- Trabzon -- 106053
Keywords: Hash Function; Hash-Based Message Authentication Code; Keccak; One Time Passwords